2019
DOI: 10.1542/peds.2018-2491
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prescribing During Pediatric Direct-to-Consumer Telemedicine Visits

Abstract: BACKGROUND AND OBJECTIVES: Use of commercial direct-to-consumer (DTC) telemedicine outside of the pediatric medical home is increasing among children, and acute respiratory infections (ARIs) are the most commonly diagnosed condition at DTC telemedicine visits. Our objective was to compare the quality of antibiotic prescribing for ARIs among children across 3 settings: DTC telemedicine, urgent care, and the primary care provider (PCP) office. METHODS:In a retrospective cohort study using 2015-2016 claims data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
136
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 174 publications
(151 citation statements)
references
References 41 publications
10
136
1
4
Order By: Relevance
“…Evidence from a previous retrospective cohort study comparing the quality of antibiotic prescribing for acute RTIs among children across three settings, demonstrated that receiving a guideline-concordant antibiotic prescription was less likely at telemedicine visits compared with matched visits at other clinical settings (i.e. urgent care, GP) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a previous retrospective cohort study comparing the quality of antibiotic prescribing for acute RTIs among children across three settings, demonstrated that receiving a guideline-concordant antibiotic prescription was less likely at telemedicine visits compared with matched visits at other clinical settings (i.e. urgent care, GP) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis by Ray et al of 4600 pediatric telemedicine visits for acute respiratory tract infections found that children at telemedicine visits were more likely to receive antibiotics and less likely to receive antibiotic management concordant with pediatricspecific national guidelines compared to children seen by their primary care providers and by urgent care providers. 101 The authors of that study also emphasize the need for AS initiatives targeting direct-to-consumer telemedicine services.…”
Section: Post-acute and Long-term Care Facilitiesmentioning
confidence: 99%
“…Telemedicine has not been thoroughly assessed in pediatric care. Some studies conducted in pediatric telemedicine show an increased rate of antibiotic treatment and care recommendations inconsistent with up to date guidelines [18]. Studies conducted in adult patients similarly show a higher incidence of inappropriate pharmacological treatment [19], a guideline adherence rate of less than 60% and even the provision of a wrong diagnosis or no diagnosis at all in more than 23% of cases [20].…”
Section: Discussionmentioning
confidence: 99%